U/Pb detrital zircon geochronology and Nd isotopes from Paleozoic metasedimentary rocks of the Marañon Complex: insights on the proto-Andean tectonic evolution of the Eastern Peruvian Andes - Cardona Molina, Agustín (2006)
Páginas 208-211.